1976
DOI: 10.1161/01.cir.54.5.805
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of pulmonary vascular disease in complete transposition of the great arteries.

Abstract: SUMMARY Forty autopsy cases of complete transposition of the great arteries (TGA) and 22 autopsy cases of ventricular septal defect (VSD) were analyzed histologically for evidence of vascular damage due to pulmonary vascular disease (PVD). Positive correlations were generally observed between an index of pulmonary vascular disease (IPVD) and blood pressure of pulmonary circulation. No significant difference in IPVD was found between TGA and VSD in the first five months of life, when cases of each disease were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(27 citation statements)
references
References 12 publications
1
25
1
Order By: Relevance
“…One could speculate that the common occurrence of persistent pulmonary hypertension and early progression of pulmonary vascular disease in the infants with TGA and intact ventricular septum may be related to the prenatal increase in pulmonary blood flow and prenatal alteration of the pulmonary vascular bed. [7][8][9][25][26][27] In our study, in fact, patient 1, with prenatal constriction of the ductus arteriosus, had such pulmonary vascular changes as previously described in TGA. 10 Furthermore, on review of the autopsy records at the Hospital for Sick Children, in the past 10 years, we found that 3 of 7 newborns with TGA/intact ventricular septum and preoperative death had established pulmonary vascular changes.…”
Section: Prenatal Nature Of the Ductus Arteriosus And Pulmonary Vascusupporting
confidence: 80%
“…One could speculate that the common occurrence of persistent pulmonary hypertension and early progression of pulmonary vascular disease in the infants with TGA and intact ventricular septum may be related to the prenatal increase in pulmonary blood flow and prenatal alteration of the pulmonary vascular bed. [7][8][9][25][26][27] In our study, in fact, patient 1, with prenatal constriction of the ductus arteriosus, had such pulmonary vascular changes as previously described in TGA. 10 Furthermore, on review of the autopsy records at the Hospital for Sick Children, in the past 10 years, we found that 3 of 7 newborns with TGA/intact ventricular septum and preoperative death had established pulmonary vascular changes.…”
Section: Prenatal Nature Of the Ductus Arteriosus And Pulmonary Vascusupporting
confidence: 80%
“…The thickness of the media at the radius of 100 ,um in small pulmonary arteries was measured using a previously reported method of assessment (Yamaki and Tezuka 1976;Yamaki and Wagenvoort 1981), and given in terms of mean + s.D. Comparison of the thickness of the media was made among the normal control cases and shunted or nonshunted cases in various age groups and differences between mean values were analyzed using student t-test, and a p value less than 0.05 was accepted as the level of significance.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of medial hypertrophy of small pulmonary arteries was determined using Suwa's method (Suwa and Takahashi 1971;Yamaki and Tezuka 1976;Yamaki and Horiuchi 1979) and expressed as the thickness of the media, 100 µm in radius of small pulmonary arteries (DR=1ooµm). The severity of intimal alteration of pulmonary arteries was determined according to the index of pulmonary vascular disease (IPVD) reported previously Tezuka 1976, 1979;Yamaki et al 1980;Yamaki and Wagenvoort 1981).…”
Section: Methodsmentioning
confidence: 99%